Celebrating the Life of Dr. Andrew “Andy” Bakun - Francisco E. Werner; Jürgen Alheit; Vera Agostini; Steven Bograd; John Field; Anne B. Hollowed; Salvador Lluch‐Cota; Nate Mantua; R. Ian Perry; Ryan R. Rykaczewski; Frank Schwing; Justin Suca (Fisheries Oceanography, 2026)

The northern California current on fire: consequences of a widespread and persistent anomalous pyrosome bloom - Richard D. Brodeur; Dylan G.E. Gomes; Douglas L. Draper; Elizabeth A. Daly; Samantha M. Zeman; Moira Galbraith; R. Ian Perry; James J. Ruzicka; Roxanne R. Robertson (Progress in Oceanography, 2026)

Isolation and characterisation of cell wall polysaccharides from taewa (Māori potatoes; Solanum tuberosum L.) - Cara.A. Luiten; Simon F.R. Hinkley; Nick R. Roskruge; Saii A. Semese; Anne-Louise M. Heath; Tracy L. Perry; Nancy J. Rehrer; Ian M. Sims (Food Hydrocolloids, 2026)

Functional characteristics of zooplankton bioregions along the cross-shelf gradient - Patrick R. Pata; Moira Galbraith; Kelly Young; Akash R. Sastri; R. Ian Perry; Brian P.V. Hunt (Progress in Oceanography, 2025)

Seasonal monitoring of dissolved and particulate algal biotoxins in the northern Salish Sea using high performance liquid chromatography and tandem mass spectrometry - Andrew R.S. Ross; Béatrice Ip; Mackenzie Mueller; Blair Surridge; Harry Hartmann; Navinder Hundal; Nathan Matthews; Hayleigh Shannon; Melissa Hennekes; Akash Sastri; R. Ian Perry (Harmful Algae, 2025)

Rubble persistence under ocean acidification threatened by accelerated bioerosion and lower‐density coral skeletons - Alice E. Webb; Ana M. Palacio‐Castro; Kenzie Cooke; Katherine R. Eaton; Benjamin Chomitz; Nash Soderberg; Morgan Chakraborty; Zachary Zagon; Albert Boyd; Patrick M. Kiel; Allyson DeMerlis; Chris T. Perry; et al. (Global Change Biology, 2024)
As the balance between erosional and constructive processes on coral reefs tilts in favor of framework loss under human‐induced local and global change, many reef habitats worldwide degrade and flatten. The resultant generation of coral rubble and the beds they form can have lasting effects on reef communities and structural complexity, threatening the continuity of reef ecological functions and the services they provide. To comprehensively capture changing framework processes and predict their evolution in the context of climate change, heavily colonized rubble fragments were exposed to ocean acidification (OA) conditions for 55 days. Controlled diurnal pH oscillations were incorporated in the treatments to account for the known impact of diel carbonate chemistry fluctuations on calcification and dissolution response to OA. Scenarios included contemporary pH (8.05 ± 0.025 diel fluctuation), elevated OA (7.90 ± 0.025), and high OA (7.70 ± 0.025). We used a multifaceted approach, combining chemical flux analyses, mass alteration measurements, and computed tomography scanning images to measure total and chemical bioerosion, as well as chemically driven secondary calcification. Rates of net carbonate loss measured in the contemporary conditions (1.36 kg m −2 year −1 ) were high compared to literature and increased in OA scenarios (elevated: 1.84 kg m −2 year −1 and high: 1.59 kg m −2 year −1 ). The acceleration of these rates was driven by enhanced chemical dissolution and reduced secondary calcification. Further analysis revealed that the extent of these changes was contingent on the density of the coral skeleton, in which the micro‐ and macroborer communities reside. Findings indicated that increased mechanical bioerosion rates occurred in rubble with lower skeletal density, which is of note considering that corals form lower‐density skeletons under OA. These direct and indirect effects of OA on chemical and mechanical framework‐altering processes will influence the permanence of this crucial habitat, carrying implications for biodiversity and reef ecosystem function.

Seasonal and regional variability of model-based zooplankton biomass in the Salish Sea and evaluation against observations - Karyn D. Suchy; Elise Olson; Susan E. Allen; Moira Galbraith; BethElLee Herrmann; Julie E. Keister; R. Ian Perry; Akash R. Sastri; Kelly Young (Progress in Oceanography, 2023)

Domoic acid in Canadian Pacific waters, from 2016 to 2021, and relationships with physical and chemical conditions - R. Ian Perry; Nina Nemcek; Melissa Hennekes; Akash Sastri; Andrew R.S. Ross; Hayleigh Shannon; Ryan B. Shartau (Harmful Algae, 2023)

Seasonal and spatial dynamics of the phytoplankton community in the Salish Sea, 2015–2019 - Nina Nemcek; Melissa Hennekes; Akash Sastri; R. Ian Perry (Progress in Oceanography, 2023)

Geography, environment, and colonization history interact with morph type to shape genomic variation in an Arctic fish - Sarah J. Salisbury; Robert Perry; Don Keefe; Gregory R. McCracken; Kara K. S. Layton; Tony Kess; Ian R. Bradbury; Daniel E. Ruzzante (Molecular Ecology, 2023)
Polymorphic species are useful models for investigating the evolutionary processes driving diversification. Such processes include colonization history as well as contemporary selection, gene flow, and genetic drift, which can vary between intraspecific morphs as a function of their distinct life histories. The interactive and relative influence of such evolutionary processes on morph differentiation critically informs morph‐specific management decisions and our understanding of incipient speciation. We therefore investigated how geographic distance, environmental conditions, and colonization history interacted with morph migratory capacity in the highly polymorphic fish species, Arctic Charr ( Salvelinus alpinus ). Using an 87 k SNP chip we genetically characterized recently evolved anadromous, resident, and landlocked charr collected from 45 locations across a secondary contact zone of three charr glacial lineages in eastern Canada. A strong pattern of isolation by distance across all populations suggested geographic distance principally shaped genetic structure. Landlocked populations had lower genetic diversities and higher genetic differentiation than anadromous populations. However, effective population size was generally temporally stable in landlocked populations in comparison to anadromous populations. Genetic diversity positively correlated with latitude, potentially indicating southern anadromous populations' vulnerability to climate change and greater introgression between the Arctic and Atlantic glacial lineages in northern Labrador. Local adaptation was suggested by the observation of several environmental variables strongly associating with functionally relevant outlier genes including a region on chromosome AC21 potentially associated with anadromy. Our results demonstrate that gene flow, colonization history, and local adaptation uniquely interact to influence the genetic variation and evolutionary trajectory of populations.

In Memoriam: Timothy R. Parsons (1932–2022) - R. Ian Perry (Fisheries Oceanography, 2023)
One of the world's pre‐eminent marine scientists and the founding editor of Fisheries Oceanography , Professor Timothy (Tim) R. Parsons, passed away peacefully in hospital in April 2022. He was passionate about building a holistic understanding of how pelagic organisms are interconnected in the food‐webs of the sea, and about presenting alternative methods for the management of fisheries. For these activities and many others, he was the recipient of many international awards and honours. He had a profound influence on many students and colleagues, and leaves behind a foundational body of work on fisheries oceanography.

Match/Mismatch Between Phytoplankton and Crustacean Zooplankton Phenology in the Strait of Georgia, Canada - Karyn D. Suchy; Kelly Young; Moira Galbraith; R. Ian Perry; Maycira Costa (Frontiers in Marine Science, 2022)
The Strait of Georgia, Canada, is an important region for numerous commercially and culturally important species (e.g., herring, salmon, and orcas), yet little is known about the links between lower trophic level (e.g. phytoplankton and zooplankton) phenology due to historical sampling gaps. Here, we present fourteen years (2003-2016) of data linking interannual variability in phytoplankton and zooplankton phenology in the Central Strait of Georgia, BC. Satellite-derived chlorophyll a (Chl a ) data were used to calculate spring bloom dynamics (bloom initiation, bloom intensity, and bloom magnitude). Average spring bloom initiation occurred during the last week of March in the Central Strait of Georgia. Bloom initiation occurred in mid-to-late February/early March during “early” Chl a bloom years (2004, 2005, and 2015) whereas initiation did not occur until the end of April during “late” bloom years (2007, 2008). Spring Chl a bloom initiation was significantly correlated with the North Pacific Gyre Oscillation (NPGO; r = 0.75, p < 0.01) and spring sea surface temperature (SST; r = -0.70, p < 0.01); spring blooms occurred earlier during warm years. When all environmental variables were considered together, NPGO best explained variations in spring bloom initiation (Adj R 2 = 0.53, p < 0.01) and bloom magnitude (Adj R 2 = 0.57, p < 0.01), whereas stratification best explained variations in bloom intensity (Adj R 2 = 0.38, p < 0.05). Early Chl a blooms were associated with high crustacean abundance (maximum of > 1000 ind m -3 ) but low biomass (37.5 mg m -3 ). Independent of the Chl a data, hierarchical cluster analysis revealed similar groupings of years for crustacean abundance data. Most notably, community composition in cluster Group 2 (2004, 2005, and 2015; early Chl a bloom years), was comprised of a higher proportion of small crustaceans (e.g. non-calanoid copepods) compared to the other cluster groups. To our knowledge, this study provides the first evidence linking early spring Chl a bloom timing to a shift in the crustacean community towards smaller taxa in response to multiple warm events in the Strait of Georgia. Our results show that early Chl a blooms may potentially result in a mismatch between phytoplankton and large energy-rich crustacean zooplankton, with lower abundances of the latter. In contrast, average Chl a bloom years were optimal for large-bodied euphausiids, whereas late Chl a blooms were a match for some crustaceans (e.g., medium calanoid copepods), but not others (e.g., large calanoid copepods and amphipods). We hypothesize that early bloom years may result in poorer feeding conditions for juvenile salmon and other predators in the region.

Gelatinous and soft-bodied zooplankton in the Northeast Pacific Ocean: Phosphorus content and potential resilience to phosphorus limitation - Florian Lüskow; Moira D. Galbraith; Brian P. V. Hunt; R. Ian Perry; Maarten Boersma; Evgeny A. Pakhomov (Hydrobiologia, 2022)

Responses of ichthyoplankton assemblages to the recent marine heatwave and previous climate fluctuations in several Northeast Pacific marine ecosystems - Jens M. Nielsen; Lauren A. Rogers; Richard D. Brodeur; Andrew R. Thompson; Toby D. Auth; Alison L. Deary; Janet T. Duffy‐Anderson; Moira Galbraith; J. Anthony Koslow; R. Ian Perry (Global Change Biology, 2021)
The effects of climate warming on ecosystem dynamics are widespread throughout the world's oceans. In the Northeast Pacific, large‐scale climate patterns such as the El Niño/Southern Oscillation and Pacific Decadal Oscillation, and recently unprecedented warm ocean conditions from 2014 to 2016, referred to as a marine heatwave (MHW), resulted in large‐scale ecosystem changes. Larval fishes quickly respond to environmental variability and are sensitive indicators of ecosystem change. Categorizing ichthyoplankton dynamics across marine ecosystem in the Northeast Pacific can help elucidate the magnitude of assemblage shifts, and whether responses are synchronous or alternatively governed by local responses to regional oceanographic conditions. We analyzed time‐series data of ichthyoplankton abundances from four ecoregions in the Northeast Pacific ranging from subarctic to subtropical: the Gulf of Alaska (1981–2017), British Columbia (2001–2017), Oregon (1998–2017), and the southern California Current (1981–2017). We assessed the impact of the recent (2014–2016) MHW and how ichthyoplankton assemblages responded to past major climate perturbations since 1981 in these ecosystems. Our results indicate that the MHW caused widespread changes in the ichthyoplankton fauna along the coast of the Northeast Pacific Ocean, but impacts differed between marine ecosystems. For example, abundances for most dominant taxa were at all‐time lows since the beginning of sampling in the Gulf of Alaska and British Columbia, while in Oregon and the southern California Current species richness increased as did abundances of species associated with warmer waters. Lastly, species associated with cold waters also increased in abundances close to shore in southern California during the MHW, a pattern that was distinctly different from previous El Niño events. We also found several large‐scale, synchronized ichthyoplankton assemblage composition shifts during past major climate events. Current climate projections suggest that MHWs will become more intense and thus our findings can help project future changes in larval dynamics, allowing for improved ecosystem management decisions.

Limited genetic parallelism underlies recent, repeated incipient speciation in geographically proximate populations of an Arctic fish ( Salvelinus alpinus ) - Sarah J. Salisbury; Gregory R. McCracken; Robert Perry; Donald Keefe; Kara K.S. Layton; Tony Kess; Cameron M. Nugent; Jong S. Leong; Ian R. Bradbury; Ben F. Koop; Moira M. Ferguson; Daniel E. Ruzzante (Molecular Ecology, 2020)
The genetic underpinnings of incipient speciation, including the genomic mechanisms which contribute to morphological and ecological differentiation and reproductive isolation, remain poorly understood. The repeated evolution of consistently, phenotypically distinct morphs of Arctic Charr ( Salvelinus alpinus ) within the Quaternary period offer an ideal model to study the repeatability of evolution at the genomic level. Sympatric morphs of Arctic Charr are found across this species' circumpolar distribution. However, the specific genetic mechanisms driving this morph differentiation are largely unknown despite the cultural and economic importance of the anadromous morph. We used a newly designed 87k SNP chip to investigate the character and consistency of the genomic differences among sympatric morphs within three recently deglaciated and geographically proximate lakes in Labrador, Canada. We found genetically distinct small and large morph Arctic Charr in all three lakes consistent with resident and anadromous morphs, respectively. A degree of reproductive isolation among sympatric morphs is likely given genome‐wide distributions of outlier SNPs and high genome‐wide F ST s. Across all lakes, outlier SNPs were largely nonoverlapping suggesting a lack of genetic parallelism driving morph differentiation. Alternatively, several genes and paralogous copies of the same gene consistently differentiated morphs across multiple lakes suggesting their importance to the manifestation of morphs. Our results confirm the utility of Arctic Charr as a model for investigating the predictability of evolution and support the importance of both genetic parallelism and nonparallelism to the incipient speciation of Arctic Charr morphs.

Developing a Social–Ecological–Environmental System Framework to Address Climate Change Impacts in the North Pacific - Steven J. Bograd; Sukyung Kang; Emanuele Di Lorenzo; Toyomitsu Horii; Oleg N. Katugin; Jackie R. King; Vyacheslav B. Lobanov; Mitsutaku Makino; Guangshui Na; R. Ian Perry; Fangli Qiao; Ryan R. Rykaczewski; et al. (Frontiers in Marine Science, 2019)

Better Regional Ocean Observing Through Cross-National Cooperation: A Case Study From the Northeast Pacific - John A. Barth; Susan E. Allen; Edward P. Dever; Richard K. Dewey; Wiley Evans; Richard A. Feely; Jennifer L. Fisher; Jonathan P. Fram; Burke Hales; Debby Ianson; Jennifer Jackson; Kim Juniper; et al. (Frontiers in Marine Science, 2019)

Carbon dioxide enrichment alters predator avoidance and sex determination but only sex is mediated by GABAA receptors - Jean-Claude Abboud; Edgar A. Bartolome; Mayra Blanco; Annalise C. Kress; Ian Y. Ellis; Perry K. Yazzolino; Kamrin I. Sorensen; James R. Winslow; David A. Cleary; Hugh Lefcort (Hydrobiologia, 2019)

A decision support tool for response to global change in marine systems: the IMBER ‐ ADA pT Framework - Alida Bundy; Ratana Chuenpagdee; Sarah R Cooley; Omar Defeo; Bernhard Glaeser; Patrice Guillotreau; Moenieba Isaacs; Makino Mitsutaku; R Ian Perry (Fish and Fisheries, 2016)
Global change is occurring now, often with consequences far beyond those anticipated. Although there is a wide range of assessment approaches available to address‐specific aspects of global change, there is currently no framework to identify what governance responses have worked and where, what has facilitated change and what preventative options are possible. To respond to this need, we present an integrated assessment framework that builds on knowledge learned from past experience of responses to global change in marine systems, to enable decision‐makers, researchers, managers and local stakeholders to: (i) make decisions efficiently; (ii) triage and improve their responses; and (iii) evaluate where to most effectively allocate resources to reduce vulnerability and enhance resilience of coastal people. This integrated assessment framework, IMBER ‐ ADA pT is intended to enable and enhance decision‐making through the development, a typology of case‐studies providing lessons on how the natural, social and governance systems respond to the challenges of global change. The typology is developed from a database of case‐studies detailing the systems affected by change, responses to change and, critically, an appraisal of these responses, generating knowledge‐based solutions that can be applied to other comparable situations. Fisheries, which suffer from multiple pressures, are the current focus of the proposed framework, but it could be applied to a wide range of global change issues. IMBER ‐ ADA pT has the potential to contribute to timely, cost‐effective policy and governing decision‐making and response. It offers cross‐scale learning to help ameliorate, and eventually prevent, loss of livelihoods, food sources and habitat.

Development of 26 novel microsatellite makers for the round whitefish (Prosopium cylindraceum) and successful polymorphic cross-specific amplification of seven previously developed salmonid markers - Gregory R. McCracken; Kristen L. Wilson; Hilary T. Brewis; Meghan C. McBride; Ian Paterson; Robert Perry; Donald Keefe; Daniel E. Ruzzante (Conservation Genetics Resources, 2014)

Development of 17 novel microsatellite markers for the longnose sucker (Catostomus catostomus) and successful cross-specific amplification of 14 previously developed markers from congeneric species - Gregory R. McCracken; Kristen L. Wilson; Ian Paterson; Robert Perry; Donald Keefe; Daniel E. Ruzzante (Conservation Genetics Resources, 2014)

Scale issues in marine ecosystems and human interactions - R. Ian Perry; Rosemary E. Ommer (Fisheries Oceanography, 2003)
Understanding the reciprocal interactions between humans and marine ecosystems has several fundamental difficulties, in particular compatible methodologies and different analytical scales. The issue of scale is central, as the scales chosen for studies of marine systems and human interactions can constrain recognition of the drivers and responses of these systems to global changes. The essential task is to discover how to combine social and natural science scale analyses to understand the impact of natural systems on people and the impact of people on natural systems. We identify characteristic spatial, temporal and organizational scales in marine ecosystems and human interactions, and the difficulties inherent in their cross‐disciplinary application. An approach is suggested focusing on communities of fish and fishers that makes explicit: (1) the need to manage marine resources in such a way as to encompass global to local scales; (2) recognition of the complementary nature of organizational scales between the natural and social sciences and use of appropriate natural science scales in the development of management policies; (3) the need to be aware of shifting temporal baselines and the representative nature of the data over time, for both social and natural sciences; and (4) caution regarding predictive models when humans are included. In terms of methodologies, good scale matches occur across large‐scale social and natural science models and surveys, but problems remain in small‐scale qualitative social studies and in cross‐scale studies. Cumulative case studies appear to provide the best approach, although ‘integrating up’ remains a challenge. Natural and social scientists need to work together to identify these issues of ecosystem processes and human interactions, and their appropriate scales.

DIETS OF FIN, SEI, AND SPERM WHALES IN BRITISH COLUMBIA: AN ANALYSIS OF COMMERCIAL WHALING RECORDS, 1963–1967 - Rowenna D. Flinn; Andrew W. Trites; Edward J. Gregr; R. Ian Perry (Marine Mammal Science, 2002)
A bstract Diets of fin ( Balaenoptera physalus ), sei ( Balaenoptera borealis ), and sperm whales ( Physeter macrocephalus ) were estimated from the stomach contents of individuals killed along the British Columbia coast from 1963 to 1967. The dominant prey types of fin whales were euphausiids, with minor contributions from copepods and fish. Sei whale stomachs contained primarily copepods in three years, whereas euphausiids or a variety of fish dominated the diet in the other two years. Sperm whales consumed primarily North Pacific giant squid ( Moroteuthis robusta ), but secondary prey differed between males and females. Female sperm whales frequently consumed ragfish ( Icosteus spp.) and other fish, whereas the male diet also contained rockfish ( Sebastes spp.). The high abundance of euphausiids along the British Columbia coast likely contributed to the presence of a summer resident population of fin whales. The high abundance of large copepods farther north probably influenced the migration of sei whales through the offshore waters of British Columbia. Sperm whale stomach contents differed by sex reflecting location and possibly breeding behaviors.

High abundance of larval rockfish over Cobb Seamount, an isolated seamount in the Northeast Pacific - John F. Dower; R. Ian Perry (Fisheries Oceanography, 2001)
The larval fish community in the region of Cobb Seamount (500 km west of Oregon) is dominated by myctophid species commonly encountered in the subarctic North Pacific. However, during a survey in June 1992, the ichthyoplankton community within 30 km of the seamount summit was almost completely dominated by larvae of various rockfish ( Sebastes ) species. Given their very small size (and hence very young age) and the fact that they occurred only rarely in samples collected > 30 km from the seamount summit, we conclude that these Sebastes larvae were produced locally over Cobb Seamount. Previous studies have shown that the Cobb fish fauna is dominated by various Sebastes spp. and that, unlike other fish present on the seamount, the rockfish populations may be self‐recruiting. We suggest that a persistent clockwise (i.e. downwelling) eddy, consistent with a stratified Taylor cone, plays a critical role in retaining larval rockfish over Cobb Seamount and may contribute to the process of self‐recruitment. The key to the success of rockfish on Cobb and other shallow Northeast Pacific seamounts seems to be linked to their viviparous life history.

Environmental influences on the availability of smooth pink shrimp, Pandalus jordani , to commercial fishing gear off Vancouver Island, Canada - R. Ian Perry; James A. Boutillier; Michael G.G. Foreman (Fisheries Oceanography, 2000)
Short time scale (less than seasonal) variability in commercial catch rates of smooth pink shrimp, Pandalus jordani, off the west coast of Vancouver Island, Canada, was examined in relation to changes in environmental conditions. Catch per unit of effort (CPUE) data were used as a proxy for catchability to identify environmental conditions affecting the availability of shrimp to the two main gear types in this fishery: otter trawls and beam trawls. Correlogram analyses of the 1996 CPUE (log‐transformed) data from each gear type, and autocorrelation analyses of wind stress, tidal current speed, sea surface temperature and salinity, and hours of bright sunshine (the latter three as residuals from their seasonal trends) for 1996 indicated a mean decorrelation time scale of 7.7 days. This was used to construct smoothed time series of these CPUE and environmental data for 1996. Multiple regression analyses with CPUE as the dependent variable and the environmental data as independent variables were significant, explaining 44% of the variability in otter‐trawl data and 35% of the beam‐trawl variability. Three hypotheses are proposed to explain these results, involving interactions between the shrimp’s behaviour and environmental conditions. A significant proportion of the within‐season variability in CPUE (and therefore in the availability of shrimp to fishing gear) for P. jordani off Vancouver Island can result from variations in environmental conditions which, if included in stock analyses, should reduce the variability of population abundance estimates.

A framework for providing scientific advice for the management of new and developing invertebrate fisheries - R. Ian Perry; Carl J. Walters; James A. Boutillier (Reviews in Fish Biology and Fisheries, 1999)